Oral glucose tolerance test significantly impacts the prevalence of abnormal glucose tolerance among Indian women with polycystic ovary syndrome: lessons from a large database of two tertiary care centers on the Indian subcontinent - Ganie, Mohd Ashraf; Dhingra, Atul; Nisar, Sobia; Sreenivas, Vishnubhatla; Shah, Zaffar Amin; Rashid, Aafia; Masoodi, Shariq; Gupta, Nandita (Fertility and sterility, 2016)
To estimate the prevalence of abnormal glucose tolerance (AGT) among Indian women with polycystic ovary syndrome (PCOS) and analyze the role of oral glucose tolerance (OGTT) test on its estimation. Cross-sectional clinical study. Tertiary care center. A total of 2,014 women with PCOS diagnosed on the basis of the Rotterdam 2003 criteria were enrolled, and the data of 1,746 subjects were analyzed. In addition to recording clinical, biochemical, and hormone parameters, a 75 g OGTT was administered. Prevalence of AGT and impact of age, body mass index (BMI), family history, and OGTT on its prevalence. The mean age of subjects was 23.8 ± 5.3 years, with a mean BMI of 24.9 ± 4.4 kg/m2. The overall prevalence of AGT was 36.3% (6.3% diabetes and 30% impaired fasting plasma glucose/impaired glucose tolerance) using American Diabetes Association criteria. The glucose intolerance showed a rising trend with advancing age (30.3%, 35.4%, 51%, and 58.8% in the second, third, fourth, and fifth decades, respectively) and increasing BMI. Family history of diabetes mellitus was present in 54.6% (953/1,746) subjects, and it did not correlate with any of the studied parameters except waist circumference and BMI. Sensitivity was better with 2-hour post-OGTT glucose values as compared with fasting plasma glucose, since using fasting plasma glucose alone would have missed the diagnosis in 107 (6.1%) subjects. We conclude that AGT is high among young Indian women with PCOS and that it is not predicted by family history of type 2 DM. OGTT significantly improves the detection rate of AGT among Indian women with PCOS.